2016
DOI: 10.1111/are.13014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacing soybean meal with rubber seed meal on digestive enzyme activity, nutrient digestibility and retention in tilapia (Oreochromis niloticus × Oreochromis aureus)

Abstract: A feeding trial was conducted to evaluate the effects of replacing soybean meal (SBM) with rubber seed meal (RSM) on digestive enzyme activity, nutrient digestibility and retention in juvenile tilapia (Oreochromis niloticus 9 Oreochromis aureus). Five isonitrogenous and isoenergetic diets were formulated with 0 (control), 100, 200, 300 and 400 g kg À1 RSM replacing graded levels of SBM respectively. Each diet was randomly assigned to triplicate groups of 30 fish (initial average weight 5.2 g) per aquarium in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
2
6
1
Order By: Relevance
“…The crude fibre value was similar to the findings of and Khatun and Khan (2015) [26] but higher than the values reported by Sharma et al (2014) [13] , Suprayudi et al (2014) [14] , [16] , Deng et al (2017) [18] , Aguihe et al (2017) [1] , Udo et al (2018) [20] , Ahaotu (2018) [19] and Farr et al (2019) [23] and lower than the values reported by Hossain et al (2015) [15] . In the present study, the total ash in RSM was found to be similar to the findings of Sharma et al (2014) [13] , Suprayudi et al (2014) [14] , Hossain et al (2015) [15] , Khatun et al (2015) [16] , Khatun and Khan (2015) [26] , Pha-obnga et al (2016) [17] and Farr et al (2019) [23] but lesser than the observation made by Chanjula et al (2011) [25] , Deng et al (2017) [18] , Oluodo et al (2018) [22] , Udo et al (2018) [20] , Aguihe et al (2017) [1] and Ahaotu (2018) [19] . The NFE value was similar to the values reported by Udo et al (2018) [20] and Deng et al (2017) [18] and contradicts with Suprayudi et al (2014) [14] , Hossain et al (2015) [15] , Khatun and Khan (2015) [26] and Aguihe et al (2017) [1] .…”
Section: Results and Discussion Proximate Composition Of Fresh/raw And Processed Rubber Seed Mealsupporting
confidence: 87%
See 3 more Smart Citations
“…The crude fibre value was similar to the findings of and Khatun and Khan (2015) [26] but higher than the values reported by Sharma et al (2014) [13] , Suprayudi et al (2014) [14] , [16] , Deng et al (2017) [18] , Aguihe et al (2017) [1] , Udo et al (2018) [20] , Ahaotu (2018) [19] and Farr et al (2019) [23] and lower than the values reported by Hossain et al (2015) [15] . In the present study, the total ash in RSM was found to be similar to the findings of Sharma et al (2014) [13] , Suprayudi et al (2014) [14] , Hossain et al (2015) [15] , Khatun et al (2015) [16] , Khatun and Khan (2015) [26] , Pha-obnga et al (2016) [17] and Farr et al (2019) [23] but lesser than the observation made by Chanjula et al (2011) [25] , Deng et al (2017) [18] , Oluodo et al (2018) [22] , Udo et al (2018) [20] , Aguihe et al (2017) [1] and Ahaotu (2018) [19] . The NFE value was similar to the values reported by Udo et al (2018) [20] and Deng et al (2017) [18] and contradicts with Suprayudi et al (2014) [14] , Hossain et al (2015) [15] , Khatun and Khan (2015) [26] and Aguihe et al (2017) [1] .…”
Section: Results and Discussion Proximate Composition Of Fresh/raw And Processed Rubber Seed Mealsupporting
confidence: 87%
“…They found the crude protein content as 11.50, 14.94, 12.19 and 10.30% respectively. However, the crude protein value in the present study contradicts with Sharma et al (2014) [13] , Suprayudi et al (2014) [14] , Hossain et al (2015) [15] , Khatun et al (2015) [16] , Pha-obnga et al (2016) [17] , Aguihe et al (2017) [1] , Deng et al (2017) [18] , Ahaotu (2018) [19] , Udo et al (2018) [20] , Kouakou et al (2018) [21] , Oluodo et al (2018) [22] , Farr et al (2019) [23] , who reported higher values in their experiments. The ether extract of RSM was similar to the observation made by Tean et al (2002) [11] , Samkol et al (2002) [24] , Aguihe et al (2017) [1] , Oluodo et al (2018) [22] and Kouakou et al (2018) [21] but lesser than the values observed by Chanjula et al (2011) [25] , Sharma et al (2014) [13] , Suprayudi et al…”
Section: Results and Discussion Proximate Composition Of Fresh/raw And Processed Rubber Seed Mealcontrasting
confidence: 78%
See 2 more Smart Citations
“…The starch fraction of the diet is considered highly digestible with apparent digestibility coefficients (ADC) of 90%, up to 99% in Nile tilapia (Amirkolaie et al, 2006;Haidar et al, 2016;Leenhouwers et al, 2007a). The ADC of the total carbohydrate fraction has been found to be as low as 30-60% (El-Saidy and Gaber, 2003;Deng et al, 2016) and as high as 80-2 90% for Nile tilapia (Tran-Ngoc et al, 2016;Sintayehu et al, 1996). The large variation in the digestibility of the total carbohydrate fraction is mainly caused by differences in the total dietary fibre fraction.…”
Section: Introductionmentioning
confidence: 99%